(3TQM GdQSGdI GdMSjfIs - (3GdCOfhj, MSjf, J (B1148s
(3ChdgG (B:s
(3jG ef habfG dhXGFa GdHMK hcdeI jG eTJQcI Hjf GdCMhGd GdKdGKI adG jMJGL Edi JhLg GdYdGeI hGdeQGO HgG ZGjI eYfGgG hgj GdELGHI hGdJhajb dZI LYd HMK GdCSHGH eJhGabI fMh GdeSHH hGUWdGMG Ndb GdbOQI Ydi GdWGYI (B...s
(3BNQgG (B:s
(3hJGSYgG Cf dG jMJSH Cf NUeg MbjQ hVYja dFdG jDOj GSJMbGQg Edi UOhQ cdGe SNja ajhdj eZdhH GdNUe GdVYja HGdEaMGe eY Cf gPG CTfY hLhg GdEdRGe hYdi Gddg GdJhcd hHg GdGYJUGe JeJs
(3JHUQI GdYfhGf (B:s
(3GdQSGdI GdMSjfjI dMSjf Hf YHO Gddg GdCfWGcj J (B1130 (3g`s
(3JHUQI GdeDda (B:s
(3fSHJg Edjg ceG hQO aj MQO eJf GdeNWhW hceG fSHJg Edjg HYV GdagGQS hbO fSHJgG HYVgG NWC Edi MSjf Hf YHO Gddg LdHj GdCeGSj hdcfg Jhaj (B1050 (3g` Cj bHd haGI eDda GdeJf HeGFI YGe (B!s
(3GdJhKjbGJ GdeQLYjI (B:s
(3JMaI GdeMHjf dYHO GdQMef GdeOfj GdCfUGQj (B1\81s
Keywords: (3GdadSaI hGdefWbs